2020
DOI: 10.1037/edu0000428
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding attention and partial word learning through interactive coviewing of educational media: An eye-tracking study with low-income preschoolers.

Abstract: This study was designed to examine the effects of coviewing on low-income children's attention to and understanding of novel words in educational media. In addition, we sought to understand coviewing's contribution to children's receptive and expressive word learning when some target words were repeated more or less frequently. Using a within-subjects design, 83 preschoolers viewed 2 educational media stories, 1 with an adult coviewer, and the other without, in a counterbalanced approach. Eye-tracking technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…This direct approach may not be typical of how adults interact with children and could have limited the agent's ability to elicit positive emotional responses. Our analysis also suggested that dialogue did not lead to a significantly higher level of visual attention during reading, while other studies suggested that children more frequently fixated on the educational content displayed on the screen when an adult co‐viewer commented on the content (Neuman et al, 2019 ). However, in Neuman et al, the comments were not designed to elicit children's verbal responses, but rather to label and explain the vocabulary.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This direct approach may not be typical of how adults interact with children and could have limited the agent's ability to elicit positive emotional responses. Our analysis also suggested that dialogue did not lead to a significantly higher level of visual attention during reading, while other studies suggested that children more frequently fixated on the educational content displayed on the screen when an adult co‐viewer commented on the content (Neuman et al, 2019 ). However, in Neuman et al, the comments were not designed to elicit children's verbal responses, but rather to label and explain the vocabulary.…”
Section: Discussionsupporting
confidence: 56%
“…A number of studies have suggested that increased reading engagement resulting from dialogic interaction is associated with enhanced outcomes. For example, Neuman et al (2019) used eye-tracking to show that dialogic coviewing, where an adult prompted children's attention using techniques such as repeating words, pointing to objects, or providing brief recaps of certain plot points, enhanced children's visual attention to narrative content and resulted in enhanced word learning. Troseth et al (2020) found that, when parents were prompted to utilize dialogic questioning strategies, children were more cognitively engaged as they talked more and used more diverse vocabulary.…”
Section: Dialogic Questioning During Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation analyses revealed that the restrictive media regulation strategies (restrictive mediation and monitoring) are often applied in parallel. Similarly, the active regulation strategies (active mediation and co-use) were highly correlated, indicating that they are also often applied in parallel or even simultaneously, e.g., when parents use the shared media time to provide their children with media-relevant information (interactive coviewing [ 25 ]). Technical mediation, in contrast, is applied independently of other regulation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing preschoolers' learning of receptive and expressive words with and without adults found support for this view. Even when there was no eye contact or verbal communication between the adults and children, the presence of others enabled the preschoolers accompanied by adults to learn more expressive words than did those who were unaccompanied (10). Therefore, social presence brought about by the presence of others does affect the extent to which individuals carry out common retrieval.…”
Section: Discussionmentioning
confidence: 99%